Effect of cypermethrin on the histoarchitecture of gills and liver of a freshwater catfish, Pangasianodon hypophthalmus (Asian Journal of Medical and Biological Research, 2016)
Histoarchitecture effect of cypermethrin was investigated in the gills and liver of freshwater catfish, Pangasianodon hypophthalmus (weight 60-70g) over an exposure period of 96 h as an endpoint of toxicity. The fish were exposed to five acute concentrations (0.00ml/L, 0.025ml/L, 0.050ml/L, 0.075ml/L and 0.10ml/L) and the 96 h LC50 was 0.075 ml/L. The physical reactions observed in the treated fish were erratic swimming, discolorations of the skin, loss of reflex, hyperactivities, surfacing, increasing opercula ventilation and these effects increased with increasing concentration of the toxicants and duration of exposure. The most common changes in gills histoarchitecture at all doses of cypermethrin were curl shape gill lamellae, bulged with the fusion of secondary gill lamellae, severe epithelial necrosis in gill lamellae and hypertrophy. The changes observed in the liver tissues were cloudy swelling, focal necrosis and hypertrophy of hepatocytes, degeneration of hepatocytes and cytoplasmic, extensive vacuolation of hepatocytes and pyknotic nuclei. The results of this histoarchitecture analysis of gills and liver tissues indicate a direct correlation between cypermethrin exposure and the histoarchitecture disorders.Asian J. Med. Biol. Res. December 2015, 1(3): 641-647